This sense of place/This living archive: Cocreative digitization and First Nations People's remembering - Benjamin Ridgeway; Olivia Guntarik (2017)
In 2016, we organized digital storytelling workshops with First Nations participants in Melbourne (Australia) to cocreatively "map" sites of historical significance through locative technologies. These digital memory maps allowed participants to share their oral stories about their relationships to different places with broader audiences, through a cultural walking trail mobile app from both their individual and collective perspectives. Functioning much like a museum tour guide in an outdoor setting, we named this app "Memoryscapes" as it would feature First Nations people's memories of different places, allowing interested members of the public (tourists, students, and educators) to listen to and watch the digital stories as they physically walked the trail. We found that a cocreative archival framework for digitizing these oral histories supported our work with community. Through this project, we illustrate how First Nations people's knowledges are populating the archive in forms that place the control of content back in their hands. These community-driven archives reveal how new archival practices are shifting the media landscape of representational possibilities. While calling attention to the politics of representing place, we also question the emancipatory potential of digital technologies for First Nations people.